FUTURE ENGINEER TRAINING: MOTIVATING TECHNIQUES - Novikova, Ye.; Новикова, Е. Б.; Новікова, Є. Б. (Харьковский национальный автомобильно-дорожный университет, 2016)
The motivating techniques for training future engineer are proposed. Intrinsic and extrinsic motivations in professional training have been analyzed. The peculiarities of the formation process of students’ motivation in learning language at non-language universities have been systematized. Heuristic training technology based on students’ motivation to cognitive research has been implemented.
ОБУЧЕНИЕ БУДУЩЕГО ИНЖЕНЕРА: РАЗВИТИЕ МОТИВАЦИИ
НАВЧАННЯ МАЙБУТНЬОГО ІНЖЕНЕРА: РОЗВИТОК МОТИВАЦІЇ
Keywords: intrinsic and extrinsic motivation; engineer; professional education; contextual learning; мотивация; инженер; профессиональное; контекстное обучение; мотивація; інженер; професійне; контекстне навчання; 377.1